Radiometric and Mineralogic Studies of the Granitic Complex in the Cape Nome Area Seward Peninsula, Alaska - West, W. S.; Matzko, J. J. (Geological Survey (U.S.), 1950)
Abstract: An early report on the Cape Nome area, Seward Peninsula, Alaska, stated that granitic rocks there contain allanite as a common accessory mineral. Results of studies in 1947 indicate that very little allanite is present, and that the slight amount of radioactiity of the granitic complex is attributable to the accessory minerals zircon and sphene.